Micelles in cancer nanomedicine: targeted delivery, imaging, and therapy - Amirhossein Rashnoodi; Zaynab Seraj; Niyoosha Zamani; Bahareh Khalili Najafabad (Academia Drug Development and Pharmacotherapy, 2026)
Despite advancements in oncology, conventional cancer therapies remain limited by poor specificity, systemic toxicity, and suboptimal therapeutic indices. Micellar nanostructures have emerged as a transformative platform to overcome these hurdles, leveraging their amphiphilic nature to encapsulate hydrophobic agents within aqueous biological environments. This review evaluates the current landscape of micelle-based technologies in cancer management, focusing on their integration into medical physics through diagnostic imaging and non-ionizing therapeutic modalities. We analyze the physicochemical principles governing micellar self-assembly, including the critical role of block copolymers and critical micelle concentration (CMC) in maintaining stability within complex biological media. The scope encompasses the application of micellar systems in enhancing contrast and targeting for computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET). Furthermore, the synergy between micellar delivery and non-ionizing therapies, specifically photodynamic therapy (PDT), photothermal therapy (PTT), and hyperthermia, is examined. Micellar platforms have shown potential to improve drug solubility, pharmacokinetic profiles, and tumor accumulation via both passive targeting and enhanced permeability and retention (EPR) effects, although this evidence derives predominantly from in vitro and animal studies. Current evidence highlights their potential in combination therapies and their evolving role in precision molecular imaging. Micelle-based nanomedicines represent a highly versatile strategy for advancing multimodal cancer theranostics. While their ability to bridge the gap between diagnostics and non-ionizing therapies is profound, achieving consistent clinical translation requires overcoming significant challenges in long-term biocompatibility, large-scale reproducible synthesis, and predictable behavior within the heterogeneous tumor microenvironment.